LINGUISTICS POLITENESS MARKERS IN AUSTRALIAN EMBASSY IN INDONESIA’S SOCIAL MEDIA - Hamidah Hamidah; Miftahulkhairah Anwar; Saifur Rohman (Program Studi Pendidikan Bahasa Program Pascasarjana Universitas Negeri Jakarta, 2020)
ABSTRACT: This article analyzes the types of politeness markers on the social media of Australian Embassy in Indonesia. This research used descriptive qualitative method with content analysis techniques. Data sources taken from Instagram and Facebook which retrieval during 2017. The data was selected based on educational and cultural themed. This reaserch found that there were 55 politeness markers included in 15 forms, there are semoga, kamu bisa, apakah, selamat, bentuk sapaan hormat, ayo atau yuk, bentuk sapaan akrab, sangat dianjurkan, asyik ya, tak sabar, tahukah kamu, sebaiknya, bagaimana, sukses untuk studinya, kami mendoakan yang terbaik, and kami ingin mengucapkan selamat. Keywords: politeness; politeness markers; Australian Embassy in Indonesia’s Social Media